Comparative Analysis of Hijup and Zalora E-Commerce Based on Maqasid Shariah Aspects - Nurazhari , Asri (SMART Insight, 2023)
This research uses a descriptive qualitative study and a simple comparison between the concepts of Zalora and Hijup which are the objects of study. Based on the discussion, Hijup and Zalora are among the best Fashion E-Commerce sites in Indonesia. Many Sharia Institutions such as BSM/AFSI (Indonesian Sharia Fintech Association) support and sign hijup E-commerce cooperation to support the utilization of the potential of the Indonesian sharia industry. The implementation of maqasid Sharia in Hijup, 5 safeguards such as protection of religion, soul, mind, charity and offspring can protect buyers from their rights while the implementation of maqasid Sharia in Zalora is still lacking because of Zalora's transactions also use a credit system and transactions are more using conventional banks.